Idarah Efforts in Fostering the Character of Teenagers of the Anshor Mosque in Sukajadi Village - Valen Febrina Saputri; Nurseri Hasnah Nasution; Emi Puspita Dewi (Universitas Muhammadiyah Palu, 2026)
This research is entitled Idarah Efforts in Fostering the Character of Adolescents of the Anshor Mosque in Sukajadi Village. This research is motivated by the low interest of adolescents in participating in mosque activities and the lack of optimal management (idarah) in developing adolescent character. The purpose of this study is to find out the efforts of the blood in fostering the adolescent character of the Anshor Mosque and identify the supporting and inhibiting factors. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, interviews, and documentation. The data sources were obtained from mosque administrators, mosque youth administrators, and mosque youth members. The results of the study show that idarah efforts in fostering the character of adolescents are carried out through several management functions, namely planning religious activity programs, organizing management structures, implementing coaching activities such as recitations, commemoration of Islamic holidays, and social activities, as well as supervision and evaluation of activities. The character development that is formed includes religious attitudes, discipline, responsibility, and cooperation.